Annie Bananie - Komaiko, Leah.; Cornell, Laura (New York : Harper & Row, 1987)
Sad because her best friend, Annie Bananie, is moving away, a little girl remembers all the fun they had together.
Booklist
School Library Journal
1.9
K-3
Keywords: Friendship -- Fiction; Moving, Household -- Fiction; Stories in rhyme; Friendship -- Fiction; Moving, Household -- Fiction; Stories in rhyme